Altered likelihood of brain activation in attention and working memory networks in patients with multiple sclerosis: An ALE meta-analysis - Kollndorfer, Kathrin; Krajnik, J.; Woitek, Ramona; Freiherr, Jessica; Prayer, D.; Schoepf, V. (Neuroscience and Biobehavioral Reviews, 2013)
Multiple sclerosis (MS) is a chronic neurological disease, frequently affecting attention and working memory functions. Functional imaging studies investigating those functions in MS patients are hard to compare, as they include heterogeneous patient groups and use different paradigms for cognitive testing. The aim of this study was to investigate alterations in neuronal activation between MS patients and healthy controls performing attention and working memory tasks. Two meta-analyses of previously published fMRI studies investigating attention and working memory were conducted for MS patients and healthy controls, respectively. Resulting maps were contrasted to compare brain activation in patients and healthy controls. Significantly increased brain activation in the inferior parietal lobule and the dorsolateral prefrontal cortex was detected for healthy controls. In contrast, higher neuronal activation in MS patients was obtained in the left ventrolateral prefrontal cortex and the right premotor area. With this meta-analytic approach previous results of investigations examining cognitive function using fMRI are summarized and compared. Therefore a more general view on cognitive dysfunction in this heterogeneous disease is enabled. (C) 2013 The Authors. Published by Elsevier Ltd. All rights reserved.
Keywords: Multiple sclerosis; Brain imaging; Working memory; Attention; Activation likelihood estimation; VLPFC; DLPFC; n-Back; PASAT; PVSAT